CAR T‐Cell Therapy in Hematologic Malignancies: A Voyage in Progress. Issue 1 (25th November 2019) - Holstein, Sarah A.; Lunning, Matthew A.
Abstract : The development of chimeric antigen receptor (CAR) T‐cell therapy for select hematological malignancies represents one of the most remarkable therapeutic advances in the past decade. Currently, CD19‐targeted CAR T‐cell therapy is approved for relapsed/refractory diffuse large B‐cell lymphoma and acute lymphoblastic leukemia. However, there is significant interest in the application of CAR T‐cell therapy to other hematological malignancies, including multiple myeloma, where the current focus is on the development of B‐cell maturation antigen‐directed CAR T‐cell therapy. Despite the successes achieved to date, there remain significant challenges associated with CAR T‐cell therapy and substantial research efforts are underway to develop new targets and approaches. Here, we provide an overview of the rapidly evolving landscape of CAR T‐cell therapy in hematological malignancies and look ahead at the advances that will shape the future of this field.